Effects, barriers and facilitators in predischarge home assessments to improve the transition of care from the inpatient care to home in adult patients: an integrative review - Kirchner-Heklau, Uta; Krause, Kai; Saal, Susanne (BMC health services research, 2021)
Background Predischarge home assessments (PDHA) aim to support safe discharge from hospital or rehabilitation. There is insufficient evidence on the effectiveness of PDHA. For adults with any diagnosis, we aimed to determine (1) the effects of PDHA on outcomes associated with the successful return to community living (e.g., Activities of Daily Living, falls) and (2) the associated barriers and facilitators in order to derive recommendations for clinical practice. Methods We searched Medline, EMBASE, CINAHL, five additional databases and other sources. We included individual and cluster randomized (RCT/cRCT) and controlled clinical trials comparing PDHA versus usual care/other intervention, as well as qualitative/mixed methods studies dealing with PDHA. Critical appraisal was performed according to the Cochrane risk-of-bias tool in quantitative studies and the Critical Appraisal Skills Programme (CASP) as well as the McMaster University Guidelines for Critical Review Form for qualitative studies and data extraction. Meta-analysis, thematic synthesis and integrative synthesis were performed. Results Eight RCTs ( n = 1072) and ten qualitative studies ( n = 336) met the inclusion criteria. RCTs reported a variety of outcomes ( n = 17). We are uncertain if PDHA has any effect on patient outcomes in Activities of Daily Living, quality of life, mobility and fear of falling, falls and hospital readmissions (with moderate to very low quality of the evidence). The qualitative studies revealed facilitators and barriers which should be considered by therapists when conducting PDHA. These were related to the following topics: patient safety education, patient information, patients’ acceptance of modifications and aids, functional assessment, standardization of procedures as well as the consideration of relevant patient conditions and contextual factors in PDHA. Conclusion There is no evidence from the meta-analysis for the effectiveness of PDHA. Further robust studies are needed to adapt and evaluate PDHA interventions, taking the identified stakeholders’ views on PDHA into account and following the current recommendations for the development and evaluation of complex interventions. Trial registration The review was registered and methods were reported on PROSPERO on 18th July 2018 ( CRD42018100636 ).